Implementasi HPack dan Gzip pada Optimasi Aplikasi Dengan Arsitektur Microservice - Tjut Adek, Rizal; Mulaesyi, Syibbran; Yunizar, Zara; M. Fauzan (Fakultas Ilmu Komputer, Universitas Brawijaya, 2024)
This study examines the application of microservice architecture in web application development, focusing on optimizing inter-service communication through data compression. Employing the waterfall method, the research was carried out in stages, including needs analysis, system design, implementation, and deployment. The primary goal was to overcome bottlenecks in transferring large data volumes by leveraging HPack and Gzip compression, especially for the prevalent JSON data format in inter-service communication. Testing results showed a significant reduction in response size and improved response times, affirming the effectiveness of HPack and Gzip in enhancing the performance of microservice applications. This research provides insights into microservice application optimization and recommendations for best practices in selecting data compression methods.